1998
DOI: 10.1046/j.1365-294x.1998.00321.x
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of genetic variability of South American wild rice populations (Oryza glumaepatula) with isozymes and RAPD markers

Abstract: The knowledge of population structure and genetic diversity of wild relatives of rice is needed to investigate their evolutionary history and potential use in breeding programs. Very little is known about the wild rice species (Oryza spp.), particularly those that are native to South America. A study using isozyme and RAPD markers was conducted to estimate the level of genetic diversity of four South American wild rice populations (Oryza glumaepatula) recently collected in the Amazon forest and western Brazil … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

12
68
3
11

Year Published

1999
1999
2007
2007

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 99 publications
(94 citation statements)
references
References 30 publications
12
68
3
11
Order By: Relevance
“…Nessa população verificaram-se caracteres agronômicos desejáveis, sendo a mais produtiva dentre as oito populações avaliadas (Tabelas 2 e 3). SANTOS et al (2002 e BUSO et al (1998) também observaram a separação de populações originárias da bacia hidrográfica do Rio Paraguai, região do Pantanal Matogrossense, de populações originárias da Amazônia, tanto por caracteres morfológicos como isoenzimáticos, evidenciando a diferenciação genética com o isolamento dessas populações e posterior adaptação a diferentes condições ambientais. VEASEY et al (2004) também notaram diferenças quanto ao padrão de quebra da dormência de sementes entre populações de O. glumaepatula; nas originárias da região Amazônica verificou-se dormência logo após a colheita, quebrada totalmente seis meses depois.…”
Section: Resultsunclassified
“…Nessa população verificaram-se caracteres agronômicos desejáveis, sendo a mais produtiva dentre as oito populações avaliadas (Tabelas 2 e 3). SANTOS et al (2002 e BUSO et al (1998) também observaram a separação de populações originárias da bacia hidrográfica do Rio Paraguai, região do Pantanal Matogrossense, de populações originárias da Amazônia, tanto por caracteres morfológicos como isoenzimáticos, evidenciando a diferenciação genética com o isolamento dessas populações e posterior adaptação a diferentes condições ambientais. VEASEY et al (2004) também notaram diferenças quanto ao padrão de quebra da dormência de sementes entre populações de O. glumaepatula; nas originárias da região Amazônica verificou-se dormência logo após a colheita, quebrada totalmente seis meses depois.…”
Section: Resultsunclassified
“…Two regions, with two distinct groups representing upper and lower Acre led to φ ST = 0.2061. Buso et al (1998) studied the genetic structure of wild rice populations, using isoenzymatic and RAPD markers to estimate the diversity level, in four South American wild rice populations (Oryza glumaepatula), collected in the Amazon forest and rivers in Western Brazil. The pattern of the genetic diversity among and within populations was calculated for both types of markers.…”
Section: Resultsmentioning
confidence: 99%
“…Several studies have indicated that O. glumaepatula is a self-fertilizing species (Akimoto et al, 1998;Buso et al, 1998;Ge et al, 1999). Such species are usually more homogeneous within populations but more differentiated between populations, forming pure lines within families and increasing the genetic differentiation between families by generating subdivision within the population.…”
Section: Introductionmentioning
confidence: 99%
“…Molecular markers have been used for germplasm characterization, phylogenetic and population genetic studies in O. glumaepatula and several other Oryza species (Akimoto et al, 1998;Buso et al, 1998;Ge et al, 1999;Doi et al, 2000;Bautista et al, 2001;Oliveira, 2002;Gao et al, 2002aGao et al, , 2002bGao, 2004;Brondani et al, 2005). Buso et al (1998) used isozyme and random amplified polymorphic DNA (RAPD) markers to estimate genetic parameters for four South American O. glumaepatula populations and found high values for interpopulation differentiation.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation